Book Review: Tierney, M. J., Strange, A., Parks, B. C., Fuchs, A., Dreher, A. Banking on Beijing: The Aims and Impacts of China's Overseas Development Program. Cambridge University Press, 2022 - Muhammad Farid (President University, 2022)
Since 2000, China transformed from “benefactor” that financed construction projects to strengthen political ties with recipient countries, to become “banker” for developing countries. Western governments, multilateral institutions, scholars, and journalists criticize China’s development finance for lack of quality, lack of proper supervision, as well creating debt problems, corruption, and environmental issues in host countries. On the contrary, those who are in favour of China claim that China provides flexible schemes, which are fit to the debtor’s demand.However, the debates are speculative and constructed based on incomplete data sources and case-by-case experience. There has been absence of comprehensive description about the aims and impacts of China’s development finance on empirical base. To cover the gap, Axel Dreher, Andreas Fuchs, Bradley Parks, Austin Strange, and Michael J. Tierney wrote a book titled Banking on Beijing: The Aims and Impacts of China's Overseas Development Program.